Evaluation of the association of SNP in carboxylesterase enzyme (CES1) with pharmacokinetic and adverse effects of capecitabine in breast and colorectal cancer patients - ÖZTÜRK CİVELEK, DİLEK; ÖZTÜRK, DİLEK; Yuksel, Merve Kurtan; Oztas, Ezgi; Ozhan, Gul; Turker, Aylin Altanlar; Korkmaz, Taner; Okyar, Alper; Kara, Zeliha Pala (My University, 2019)
Capecitabine is an oral prodrug and converted to 5-fluorouracil using three-step enzymatic pathways which include carboxylesterase (CES). Interindividual differences in the activities of drug-metabolizing enzymes may affect efficacy and toxicity. The aim of this study is to evaluate the association of Single nucleotide polymorphisms (SNP) in CES1 with the pharmacokinetic and adverse effects of capecitabine. Plasma samples were obtained from 7 breast and colorectal cancer patients who were treated with capecitabine-based chemotherapy (1000-1250 mg/m(2)) at 0.5, 1, 2, 3 and 4 hours following drug administration on their first day of the first cycle. The plasma concentrations of the capecitabine were determined by using a high-pressure liquid chromatography-UV detector. SNP (rs8192950) was genotyped using the reverse transcription-polymerase chain reaction. Patients were found to have heterozygote (57%), wild (29%), and mutant (14%) distributions of genotypes (p=0.909). The mean plasma area under the curve (AUC(0-4h)) was 4.60 +/- 2.25 mu g.h/mL, and maximum plasma concentration (C-max) was 3.19 +/- 2.5 mu g/mL. There were no statistically significant differences between genotypes and AUC values (p=0.2236) and the most frequently observed side effects were diarrhea (p=0.1028), asthenia (p=0.6456), anemia (p=0.6456), emesis (p=0.3499). This is the first study evaluating an association of genetic variation in CES1 (rs8192950) with pharmacokinetic and adverse effects of capecitabine. Therefore, additional study in larger groups of patients is required to support our study.